Immunodominant MHC-II (Major Histocompatibility Complex II) Restricted Epitopes in Human Apolipoprotein B. Issue 3 (29th June 2022) - Roy, Payel; Sidney, John; Lindestam Arlehamn, Cecilia S.; Phillips, Elizabeth; Mallal, Simon; Armstrong Suthahar, Sujit Silas; Billitti, Monica; Rubiro, Paul; Marrama, Daniel; Drago, Fabrizio; Vallejo, Jenifer; Suryawanshi, Vasantika; et al.
Abstract : Background: CD (cluster of differentiation) 4 + T-cell responses to APOB (apolipoprotein B) are well characterized in atherosclerotic mice and detectable in humans. CD4 + T cells recognize antigenic peptides displayed on highly polymorphic HLA (human leukocyte antigen)-II. Immunogenicity of individual APOB peptides is largely unknown in humans. Only 1 HLA-II-restricted epitope was validated using the DRB1*07:01-APOB3036 –3050 tetramer. We hypothesized that human APOB may contain discrete immunodominant CD4 + T-cell epitopes that trigger atherosclerosis-related autoimmune responses in donors with diverse HLA alleles. Methods: We selected 20 APOB-derived peptides (APOB20 ) from an in silico screen and experimentally validated binding to the most commonly occurring human HLA-II alleles. We optimized a restimulation-based workflow to evaluate antigenicity of multiple candidate peptides in HLA-typed donors. This included activation-induced marker assay, intracellular cytokine staining, IFNγ (interferon gamma) enzyme–linked immunospot and cytometric bead array. High-throughput sequencing revealed TCR (T-cell receptor) clonalities of APOB-reactive CD4 + T cells. Results: Using stringent positive, negative, and crossover stimulation controls, we confirmed specificity of expansion-based protocols to detect CD4 + T cytokine responses to the APOB20 pool. Ex vivo assessment of AIM + CD4 + T cells revealed a statistically significant autoimmune response to APOB20 but not to a ubiquitously expressed negative control protein, actin. Resolution of CD4 + T responses to the level of individual peptides using IFNγ enzyme–linked immunospot led to the discovery of 6 immunodominant epitopes (APOB6 ) that triggered robust CD4 + T activation in most donors. APOB6 -specific responding CD4 + T cells were enriched in unique expanded TCR clonotypes and preferentially expressed memory markers. Cytometric bead array analysis detected APOB6 -induced secretion of both proinflammatory and regulatory cytokines. In clinical samples from patients with angiographically verified coronary artery disease, APOB6 stimulation induced higher activation and memory phenotypes and augmented secretion of proinflammatory cytokines TNF (tumor necrosis factor) and IFNγ, compared with patients with low coronary artery disease. Conclusions: Using 3 cohorts, each with ≈20 donors, we discovered and validated 6 immunodominant, HLA-II–restricted APOB epitopes. The immune response to these APOB epitopes correlated with coronary artery disease severity.